Business model generation : a handbook for visionaries, game changers, and challengers - Osterwalder, Alexander, ....-; Pigneur, Yves, 1954- (Hoboken, NJ : Wiley, 2010)
Offers tools and techniques to systematically understand, design, and implement new business models and renovate and rework old models.
1: Canvas -- Definition of a business model -- The 9 building blocks -- The business model canvas -- 2: Patterns -- Unbundling business models -- The long tail -- Multi-sided platforms -- FREE as a business model -- Open business models -- 3: Design -- Customer insights -- Ideation -- Visual thinking -- Prototyping -- Storytelling -- Scenarios -- 4: Strategy -- Business model environment -- Evaluating business models -- Business model perspective on blue ocean strategy -- Managing multiple business models -- 5: Process -- Business model design process.
Includes bibliographical references.
Keywords: Business planning; Innovationsmanagement; New business enterprises; Social Sciences and Humanities. Management studies, Business Administration, Organizational Science -- Organization Science; Strategic planning